Geographical Zone based Cluster Head for Routing in Sparse Vehicular Networks - Brendha, R; Sinthu Janita Prakash, V (International Journal of Engineering and Technology, 2018)
Vehicular ad hoc network is a wireless communication technology that is used to provide safety and comfort transport on the roads. Routing algorithm design is one of the main challenging issues in VANET. This paper presents a Geographical Zone Based Cluster Head algorithm for Vehicular Ad hoc Networks (VANETs) to reduce the communication overhead generated by the Control Packets (CP). Depending on the area, the network can be sparsely or fully connected. The Geographical Zone Based Cluster Head Routing in Sparse network (GZCHRS) algorithm can endure network partition due to low node density in the sparse network and high node density in the urban network. This paper inspects the issues of VANETs in sparse networks. In this algorithm, the routing decision is based on vehicular density, velocity and link lifetime. The simulation results display that under rural network conditions, the Geographical Zone Based Cluster Head Routing algorithm performs well when compared to Light Weight Intersection based Traffic Aware Routing (LITAR) and Intersection-based Connectivity Aware Routing (ICAR).Â Â